UMP's hostel for needy students - Hidir, Reduan (The New Straits Times Press (M) Bhd., 2017)
UNDERPRIVILEGED and orphaned undergraduates from Universiti Malaysia Pahang (UMP) are set to have new dormitory accommodation as they pursue their tertiary education.